2022
DOI: 10.22219/jpbi.v8i2.18093
|View full text |Cite
|
Sign up to set email alerts
|

Instructıonal resources for teachıng bıology ın secondary schools ın Moro, Kwara State-Nigeria

Abstract: Instructional resources play an important role in conducting high quality education. This research assessed the availability and utilization of instructional resources in Moro Local Government Area (LGA) of Kwara State, Nigeria. Descriptive survey research was adopted for the study. A total of sixty (60) Biology teachers were randomly sampled from eighteen (18) schools in Moro Local Government Area Kwara State. Three research questions and two hypotheses guided this study. Questionnaire was used as an instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…In other words, the level of achievement or performance of learners in any subject is heavily influenced by teachers' pedagogical abilities, attitudes, and capacity to employ instructional materials to teach any subject at any level of learning. Accordingly, Abidoye et al (2022), study of instructional resources for teaching biology in secondary schools in Moro, Kwara State, Nigeria, revealed that instructional resources for teaching Biology were not available in most senior secondary schools. Stephen and Isaac (2013) also carried out a study on the influence of instructional materials on the academic performance of senior secondary school students in chemistry in Cross River State.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the level of achievement or performance of learners in any subject is heavily influenced by teachers' pedagogical abilities, attitudes, and capacity to employ instructional materials to teach any subject at any level of learning. Accordingly, Abidoye et al (2022), study of instructional resources for teaching biology in secondary schools in Moro, Kwara State, Nigeria, revealed that instructional resources for teaching Biology were not available in most senior secondary schools. Stephen and Isaac (2013) also carried out a study on the influence of instructional materials on the academic performance of senior secondary school students in chemistry in Cross River State.…”
Section: Introductionmentioning
confidence: 99%
“…Developing a comprehensive understanding of biological concepts is vital for students to effectively navigate the complexities of the living world. This understanding not only enables them to contribute actively to environmental sustainability and engage in scientific research but also empowers them to make informed decisions in an increasingly intricate biological landscape (Abidoye, Aliyu, Ahmed & Oluwole, 2022). Consequently, there has been significant emphasis on instruction, particularly at the secondary school level, aimed at ensuring comprehension of the principles and objectives outlined in the National Policy on Education (FRN, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These materials can take various forms, including visual aids, manipulatives, multimedia presentations, and technological resources. By integrating appropriate instructional materials into their teaching, educators encourage active participation and engagement among students, significantly when students can interact with and manipulate the materials (Abidoye et al, 2022).…”
Section: Introductionmentioning
confidence: 99%